Complications related to chronic supratherapeutic use of codeine containing compound analgesics in a cohort of patients presenting for codeine withdrawal. (2nd May 2018) - Cock, Victoria; Edmonds, Carolyn; Cock, Charles
Abstract: Introduction and Aims: This study aimed to compare complications arising due to the supratherapeutic use of paracetamol/codeine or ibuprofen/codeine containing compound analgesics in primary codeine‐dependent patients presenting to a drug and alcohol withdrawal service. Data was compared to determine if there was any difference in the number of complications observed between the two groups. Design and Methods: A retrospective case review of patients presenting for primary codeine dependence from 2009 to 2014. Sixty patients (42F, 36 ± 10 years) using ibuprofen/codeine and 46 (26F, 39 ± 10 years) using paracetamol/codeine containing compound analgesics were compared. A P value of <0.05 was considered significant. Results: Patients consumed similar daily doses of codeine (699 ± 45 vs. 636 ± 50 mg) with those consuming ibuprofen/codeine containing compound analgesics ingesting twice as many tablets daily (median 60 vs. 30 tablets; P < 0.0001). Complications related to supratherapeutic use of codeine containing compound analgesics occurred more commonly in patients taking ibuprofen/codeine (52/60; 87%) versus paracetamol/codeine compound analgesics (30/46; 65%) ( P < 0.01). Patients taking ibuprofen/codeine containing compound analgesics were more likely to have gastrointestinal bleeding ( P < 0.05), anaemia ( P < 0.0001) and renal tubular acidosis ( P < 0.05). There were two deaths in the group abusing ibuprofen/codeine compound analgesics. Discussion and Conclusions: In patients with primary codeine dependence, there were more complications related to the supratherapeutic use of ibuprofen/codeine versus paracetamol/codeine containing compound analgesics. The patients in both groups ingested similar total daily codeine amounts. Increased daily tablet intake in the ibuprofen/codeine group could possibly have been linked to lower codeine content per tablet.